An integrated review of architectural design and robotic planning for collective robotic construction - Agrawal, Swati; Dahiya, Abhay (Architecture Image Studies, 2024)
Most studies on Collective Robotic Construction (CRC) delineate the architectural designing and robotic route planning stages of the whole building process. A structure is built and forwarded to planners or compilers that generate assembly directions for the available robots. This has resulted in the construction of physically intricate buildings, although it complicates the planning procedure, rendering it unavailable to the architects. This study demonstrates how an Agent-Based Modelling System (ABMS) integrates CRC's building design and robotic development phases, highlighting the architect's role beyond merely designing static buildings. The whole construction pipeline is disrupted, resulting in more designer management, adjustments for limitations in the building process, broader comprehension of the procedures, and the possibility for design reconfiguring when utilizing CRC technologies. This is illustrated by introducing an ABMS for constructing a planar building utilizing a previously established CRC mechanism.